2014
DOI: 10.1007/s10803-014-2341-1
|View full text |Cite
|
Sign up to set email alerts
|

Fragile Spectral and Temporal Auditory Processing in Adolescents with Autism Spectrum Disorder and Early Language Delay

Abstract: We investigated low-level auditory spectral and temporal processing in adolescents with autism spectrum disorder (ASD) and early language delay compared to matched typically developing controls. Auditory measures were designed to target right versus left auditory cortex processing (i.e. frequency discrimination and slow amplitude modulation (AM) detection versus gap-in-noise detection and faster AM detection), and to pinpoint the task and stimulus characteristics underlying putative superior spectral processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 103 publications
(138 reference statements)
1
6
0
Order By: Relevance
“…While there has not been a single account that entirely explains all the features of ASC, the current finding that pitch discrimination was negatively correlated with autistic social traits failed to support the EPF theory (Mottron & Burack, 2001;Mottron et al, 2006). This was in line with previous studies which used group measures and reported diminished pitch discrimination in individuals with ASC across lifespan (Boets et al, 2015;Kargas et al, 2015;Yu et al, 2015). Although this study did not test individuals with ASC, its findings have an implication in investigating individual differences in pitch discrimination and specific ASC traits rather than ASC in general, reflecting the high variability and complexity across the autism spectrum.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…While there has not been a single account that entirely explains all the features of ASC, the current finding that pitch discrimination was negatively correlated with autistic social traits failed to support the EPF theory (Mottron & Burack, 2001;Mottron et al, 2006). This was in line with previous studies which used group measures and reported diminished pitch discrimination in individuals with ASC across lifespan (Boets et al, 2015;Kargas et al, 2015;Yu et al, 2015). Although this study did not test individuals with ASC, its findings have an implication in investigating individual differences in pitch discrimination and specific ASC traits rather than ASC in general, reflecting the high variability and complexity across the autism spectrum.…”
Section: Discussionsupporting
confidence: 81%
“…Superior pitch perception may be limited to children with ASC (Heaton, Hudry, Ludlow, & Hill, 2008b;Mayer et al, 2016;O'Riordan & Passetti, 2006), subgroups of children and adolescents with ASC (Eigsti & Fein, 2013;Heaton, Williams, Cummins, & Happé, 2008c) and subgroups of adults with ASC (Bonnel et al, 2010;Jones et al, 2009). Two recent studies even reported deficits in pitch discrimination in adolescents and adults with ASC (Boets, Verhoeven, Wouters, & Steyaert, 2015;Kargas, López, Reddy, & Morris, 2015). Neural sensitivity for speech pitch in Mandarin-speaking children with ASC was also found to be diminished (Yu et al, 2015).…”
mentioning
confidence: 94%
“…The observed decreases in OAE amplitudes at 1 kHz mid‐frequency region could cause reduced ability to discriminate between two sounds or impair auditory tuning [Dallos, ]. In fact, Boets, Verhoeven, Wouters, and Steyaert [] noted that children with ASD had impaired auditory tuning when compared with TD children. In addition, mammalian cochlear development is a process with both a basal (high‐frequency region) to apical (low‐frequency region) developmental gradient over several prenatal days (i.e., tonotopic development), so deficits in the 1 kHz frequency regions could give insight into a developmental window of cochlear function deficits [Lavigne‐Rebillard & Pujol, ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with autism showed superior abilities at auditory segregation when streams of melodies were completely embedded (the mean frequency of target melody matched the distractor melody), but inferior performance when streams were separated by a different mean frequency (Bouvet et al ., ). Using a gap in noise technique, inferior frequency discrimination was exhibited in autism compared to controls (Boets et al ., ). Similar to the visual modality, it seems that they show superior local processing, and similar global processing compared to control, with some decrement when transferring local information to global processing (Ouimet et al ., ; Bouvet et al ., ).…”
Section: Auditionmentioning
confidence: 97%